Current Problems Of Accounting Investment Activities Of Enterprises Of Ukraine - G.Yu. Khomenko; O.V. Voznyuk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
In connection with the strong development of production processes and the economy of the country as a whole, the question arises about attracting financial investments for the company and improving the investment climate in general. In the context of the protracted economic crisis in Ukraine, the issue of attracting and improving investment processes becomes a priority. After all, thanks to the financial investments of the investors, the enterprises are able to improve the quality of their products, to upgrade the equipment, which enables not only to lose a potential buyer, but also to enter new markets, including European ones. So, we can say that Ukraine is a rather promising country for the investor, but a range of diverse problems makes it less appealing for attracting investment resources and foreign partners. Overcoming the existing problems and implementing the proposals will create the preconditions for improving the investment climate in the country. In the study of financial investment as an accounting object it is important to note that in these market conditions, the investment process is quite important, necessary and very relevant today. This is confirmed by the annual statistics on the volume of financial investments made in the country's economy. In general, financial investments are an important element of the functioning of firms. They provide financial stability and enable companies to apply the latest technology, improve quality and put into practice ideas and inventions. Under such conditions, it is important to identify and find ways to overcome the current problems of accounting for financial investments in Ukrainian enterprises.